Magnetized radiative flow of propylene glycol with carbon nanotubes and activation energy - Ali Ghazwani, Hassan; Saleem, Muzher; Haq, Fazal (Scientific reports, 2023)
Carbon nanotubes (CNTs) have gained significant attention in the field of fluid dynamics and fluid flows due to their unique properties and the potential to enhance various aspects of fluid transport features. This article explores the behavior of Darcy–Forchheimer flow of Propylene glycol C 3 H 8 O 2 submerged single wall carbon nanotubes (SWCNT) and multi-wall carbon nanotubes (MWCNT). The flow features are examined over stretched preamble surface of sheet. Energy relation is acquired in manifestation of thermal radiation and Joule heating. Aspects of Arrhenius kinetics and chemical reaction are assimilated in mass transport relation. Furthermore, effects of intermolecular fluid friction is accounted. Flow prevailing mathematical model is acquired by implementing boundary layer assumptions. Transformations procedure is adapted to alter the dimensional model into non-dimensional one and then tackled through Runge–Kutta–Fehlberg method (RKF-45) in Mathematica. Effective consequences of influential flow controlling parameters on fluid velocity, thermal transport and concentration are inspected by plotting. Numerical computations for interesting engineering quantities like skin friction coefficient, mass and heat transfer rates are tabulated and investigated. It is noticed that thermal field boosts versus curvature variable, Eckert and Hartmann numbers. Retardation in mass concentration is noticed via Schmidt number and activation energy variable. Velocity field shows decreasing trend through porosity parameter, Hartmann number and Darcy–Forchheimer variable. Furthermore, it is noticed that magnitude of skin friction coefficient is higher for SWCNT as compared to MWCNT.